2021
DOI: 10.32598/jccnc.7.4.33.17
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Humor Training on Happiness and Life Satisfaction of Female Patients With Epilepsy

Abstract: Background: Women with epilepsy face many physical and psychological problems due to their illness. Epilepsy affects women’s motherhood, parenting role, and quality of life. Thus, in addition to medical interventions, their recovery programs should also cover psychological therapies. Accordingly, this study aimed to examine the effectiveness of humor training on happiness and life satisfaction of female patients with epilepsy. Methods: This study was conducted using a quasi-experimental method with a pretest-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Contemporaneous studies (located after data collection) support the use of humor with patients in a variety of ways and may enhance patients' own self-guided imagery. Humor training, focusing on the theory of humor and ways to see situations in new and humorous ways, (Kugler et al, 2021) showed promising results in reducing pain intensity and improving quality of life for hospitalized patients with chronic pain; and improving happiness and life satisfaction with female patients with epilepsy (Bagherzadeh Shirvan & Khodabakhshi-Koolaee, 2021). Watching comedy videos helped Turkish preoperative oncology patients have a significant reduction in anxiety, diastolic and systolic blood pressure suggesting that watching comedy videos had a positive effect on preoperative anxiety and blood pressure (Genç & Saritas, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Contemporaneous studies (located after data collection) support the use of humor with patients in a variety of ways and may enhance patients' own self-guided imagery. Humor training, focusing on the theory of humor and ways to see situations in new and humorous ways, (Kugler et al, 2021) showed promising results in reducing pain intensity and improving quality of life for hospitalized patients with chronic pain; and improving happiness and life satisfaction with female patients with epilepsy (Bagherzadeh Shirvan & Khodabakhshi-Koolaee, 2021). Watching comedy videos helped Turkish preoperative oncology patients have a significant reduction in anxiety, diastolic and systolic blood pressure suggesting that watching comedy videos had a positive effect on preoperative anxiety and blood pressure (Genç & Saritas, 2020).…”
Section: Discussionmentioning
confidence: 99%